Optimalisasi Mesin Pemotong Kentang Stik Balado - Khairil Fajar (2023)
Potato is an important crop in Indonesia utilised in various processed foods but there are still household industries that process potatoes using manual methods. Therefore, the writer conducted research on the optimization of potato cutting tools using the frame static simulation method, variations of cutting trials with blade distance from 95 mm, 90 mm, 85 mm and RULA (Rapid Upper Limb Assessment). The tool frame structure uses ASTM Steel A36 material. The results of the static simulation of the frame obtained the smallest factor of safety is 43. The optimization step that can be done is to change the frame dimensions to 20 x 20 x 3 mm and use SS 34 material. For the trial variation, the highest capacity and efficiency of cutting tools were obtained in trial variation 2 with blade distance 90 mm with a value of 98.5 kg/hour and 62.09%. The efficiency of the tool has met the efficiency standard with a result of 62.09% of the specified 60%-70% range. The application of RULA on the tool gets a final score of 3 so adjustments need to be made so that the worker's posture is comfortable.